Fashion Inspired by Architecture: The Interrelationship between Mashrabiya and Fashion World - Ayten Özsavaş Akçay (Tarih Kültür ve Sanat Araştırmaları Dergisi, 2018)
The relationship between architecture and fashion fields have received many studies. Some researches have considered them as parallel worlds, while others have proven that the link is an interrelationship. Generally, architecture and fashion have many common sources: art, science, and technology. This makes them sometimes close worlds, and in many other cases, they are mixed. However, it is wise to assume that the best situation when one field becomes a source to another, and they support each other within a logical visible relationship. Architecture gives inspiration to fashion, per contra fashion achieves notability for an architectural figure or element.